A method for the experimental identification of equivalent viscoelastic models from vibration of thin plates. (15th May 2021) - Grosso, Pasquale; Felice, Alessandro De; Sorrentino, Silvio
Highlights: Aim of the present study: identification of equivalent viscoelastic models for layered thin walled structures, obtained from vibration measurement only, able to fit the experimental data on a relatively wide frequency range by means of a minimum number of parameters. Circle-fit technique: the classical circle-fit technique is extended to include the possibility of identifying the damping properties of vibrating structures by means of non-conventional viscoelastic models, like fractional derivative models. Fractional derivative rheological models: the Fractional Kelvin model is adopted for identifying the parameters of a complex Young's modulus in the frequency domain, modelling the viscoelastic properties of a homogenized structure. Experimental results: analysis of vibrating plates made of Quiet Aluminum (QA) and of vibrating Aluminum plates coated by damping pads (ADP), assessing the accuracy of the identified parameters by comparison of numerically simulated with experimentally measured FRFs. Abstract: Aim of the present study is the identification of equivalent viscoelastic models for layered thin walled structures, obtained from vibration measurement only, able to fit the experimental data on a relatively wide frequency range by means of a minimum number of parameters. A novel approach is proposed, based on a definition of an equivalent modal damping ratio applied to the circle-fit technique, to overcome the difficulties related to the identification of modal parameters when adopting non-conventional viscoelastic models. When the structural internal dissipative effects are dominant, this procedure identifies the parameters of an equivalent Young's modulus in the frequency domain, representing the viscoelastic properties of a homogenized structure as a scalar function with frequency-dependent real and imaginary parts. The proposed procedure is applied to the analysis of Aluminum plates coated by damping pads and of plates made by Quiet Aluminum. To fit the experimentally found equivalent modal damping ratios, several viscoelastic models are adopted and compared (viscous, hysteretic, generalized Maxwell, fractional derivative damping, and in particular the Fractional Kelvin-Voigt model), assessing the accuracy of the identified parameters by comparison of numerically simulated with experimentally measured frequency response functions.